The impact and incidence of altered body image in patients with head and neck tumors: a systematic review. Issue 4 (14th June 2018) - Manier, Karra K; Rowe, Lindsay S; Welsh, Judith; Armstrong, Terri S
Abstract: Body image dissatisfaction is a common issue among patients with cancer and is associated with difficulty coping, anxiety, and depression. Patients with tumors involving the head and neck are at increased risk of body image dissatisfaction due to the visible disfigurement that can occur from their illness and its treatment. Patients with primary central nervous system (CNS) malignancies often face similar tumor-related and treatment-related effects, yet there is limited research conducted in this population. Our aim was to perform a systematic review of the literature on body image in patients with tumors of the head and neck, and identify factors associated with body image alterations during treatment, with the intention of applying these approaches to those with CNS disease. A systematic search of PubMed and EMBASE was performed using predefined criteria. Nine studies met the inclusion criteria and were selected for review. The literature collected showed a relationship between body image and age, depressive symptoms, and tumor grade or stage. In addition, body image disturbance had an impact on patients' daily functioning and psychosocial indices including anxiety, coping, and body reintegration. Evaluation of the impact of body image alterations in patients with CNS tumors is needed to direct clinical care, explore research opportunities, and improve patient quality of life.